ANALISIS PENGARUH RASIO KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR TAHUN 2018-2022 - Ambarwati, Desi (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Main Purpose - This research was conducted with the aim of testing the effect of leverage, liquidity, profitability on company value. The research population is manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2018-2022. Design/methodology/approach - The sample obtained was 18 manufacturing companies based on purposive sampling criteria. Data analysis used descriptive statistics, multiple linear regression analysis, normality test and hypothesis testing with SPSS version 22.0. Main Findings - Based on the case phenomenon experienced by PT. Wijaya Karya (Persero) Tbk (WIKA) experienced a decline in performance due to a decrease in net profit generated by the company which resulted in the value per share decreasing. So the research results show that leverage has a positive effect on company value, liquidity has no effect on company value, profitability has a positive effect on company value and dividend policy has a positive effect on company value. Theory and Practical Implications - So the implication in this research is to know the level of increase or decrease in company value based on the company's ability to fulfill its obligations, earn profits and distribute dividends by the company which are taken into consideration when investing in the company. The level of company liquidation does not influence investors to invest because investors usually consider the profits generated by the company. NoveltyWith a different manufacturing research object and research period than previous research